Effect Anti VEGF Intravitreal to Central Retinal Vein Occlusion - Tiara Mayasari; Ramzi Amin; AK Ansyori (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2018)
Introduction. The cause of blood vessels abnormalities in the retina in addition to diabetes is obstruction in the veins. In general, retinal vein blockages are distinguished in two types i.e. blockage of retinal veins (BRVO) and obstruction of the central vein of the retina (CRVO). Reported a case of a central retinal vein occlusion with intravitreal anti-injection treatment of a VEGF Bevacizumab. Case presentation. A man, Mr. T, aged 52 years, with an address outside the city, the work of the foreman, came to RSMH's eye on October 2014. Anamnesis the main complaint of the right eye eyesight was suddenly dark since, one day before. One day before go to hospital, the sufferer complained about the right eye suddenly until it felt dark. He also complain often headaches without nausea and vomiting since before his right eye vision becomes blurred. Intravitreal anti-VEGF injection in these patients is planned to be re-done 4-6 weeks after the first injection if there has been no improvement in his vision. Evaluation of the effectiveness of intravitreal Bevacizumab anti-VEGF therapy through sharp improvement of vision, clinical features and anatomical improvement. Conclusion. A case of central retinal vein occlusion was reported in a 52-year-old male. After anamnesis, ophthalmologic examination and investigations, a diagnosis of CRVO is managed by intravitreal Anti VEGF injection.